Exploratory factor analysis for mathematics identity among secondary school students / Junaida Md Said ... [et al.] - Md Said, Junaida; Raja Maamor Shah, Raja Lailatul Zuraida; Yunus, Riyan Hidayat; Jamian, Nurul Husna (Universiti Teknologi MARA, Perak, 2023)
Currently, there is not widely accepted or universally recognized measure that captures a singular identity for mathematics due to inconsistent measurement methods used in research on this topic The problematic nature of students' relationship with mathematics has prompted researchers to examine the issue through the perspective of identity. This research examined the alignment between the items on the adapted questionnaire related to mathematics identity load on the theorized sub-constructs by conducting instrument validation. Cluster sampling method was employed in this study, involving 213 participants. A questionnaire comprising 19 items was administered to secondary school students. Then, the exploratory factor analysis (EFA) was utilized to categorize the different components present in the questionnaire. Additionally, Cronbach's Alpha was calculated to assess the internal validity and reliability of the questionnaire, ensuring the consistency and accuracy of the instrument. The study revealed that there are three main dimensions which are mathematics recognition, mathematics learning performance and competence, and mathematics career interest that can be classified by 13 items. The result led to formulate a new set of questionnaires. The new set of questionnaires will be distributed for further research to proceed on confirmatory factor analysis (CFA).